Dark side of a bio-based and biodegradable plastic? Assessment of pathogenic microbes associated with poly(butylene succinate-co-adipate) under ambient and future climates using next-generation sequencing - Juncheed, Kantida; Tanunchai, Benjawan; Wahdan, Sara Fareed Mohamed; Thongsuk, Katikarn; Schädler, Martin; Noll, Matthias; Purahong, Witoon (Frontiers in Plant Science, 2022)
Bio-based and biodegradable plastic mulching films have been proposed to replace the non-biodegradable plastic mulch films to solve plastic pollution problems in agricultural soils. However, the impact of bio-based and biodegradable plastics on plants and human health remains largely unexplored. Here, we aimed to assess the risk under field conditions of a bio-based and biodegradable poly(butylene succinate-co-adipate) (PBSA), a widely used mulching film as carrier of potential pathogenic microorganisms (bacteria and fungi) at ambient and future climate conditions. Overall, we affiliated 64 fungal and 11 bacterial operational taxonomic units (OTUs) as pathogens by using Next Generation Sequencing approach. Our results revealed that PBSA hosted at least 54 plant pathogens, of which 52 were classified as fungi, while the other two were bacteria. Most fungal plant pathogens were able to withstand the anticipated future climate changes. We detected 13 fungal and eight bacterial OTUs, which were classified as opportunistic human pathogens. Only one bacterial OTU (Enterococcus faecium) was assigned to a human pathogen. While future climate conditions only significantly impacted on the presence and frequency of detection of few pathogens, incubation time were found to significantly impacted on 9 pathogens. This results demonstates the temporal dynamics of pathogens associated with PBSA. The threats to plant and human health were discussed. We emphasize that the risks to human health are relatively low because we mainly found opportunistic pathogens associated with PBSA and the amount are comparable to the plant debris. However, the risks to plant health may be considered as moderate because many plant pathogens were discovered and/or enriched in PBSA. Furthermore, in soil environments the pathogenic risk of plastic is highly depending on the surrounding soil pathobiome where plastic is being decomposed.